2021
DOI: 10.1111/ajsp.12461
|View full text |Cite
|
Sign up to set email alerts
|

Majority world successes and European and American failure to contain COVID‐19: Cultural collectivism and global leadership

Abstract: United Nations and World Health Organization data show a positive correlation, r = .53, p < .0001, N = 189, between COVID‐19 infection rates and the human development index (HDI). Less wealthy, less educated countries with lower life spans were also more successful in maintaining lower fatality rates, r = .46, p < .0001, N = 189 whereas 9 of the top‐10 countries in the world in per capita fatalities due to COVID‐19 were Western societies high in HDI. Similar positive correlations were found between COVID‐19 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 26 publications
2
40
0
3
Order By: Relevance
“…In many regards, the preventative actions advised by the WHO are luxuries of those living in more privileged circumstances and the wealthier economies of the Global North. But despite these disparities, Liu (2021) reported that the Human Development Index correlated positively with infection rates ( r = .52) and fatality statistics ( r = .46). This indicates that as of the end of 2020, developing countries had reported fewer per capita infections and deaths compared to the wealthy countries such as those in the OECD.…”
Section: Public Health and The Covid‐19 Crisis: The Limits Of Individualism And Individual Explanations Of Behaviourmentioning
confidence: 99%
“…In many regards, the preventative actions advised by the WHO are luxuries of those living in more privileged circumstances and the wealthier economies of the Global North. But despite these disparities, Liu (2021) reported that the Human Development Index correlated positively with infection rates ( r = .52) and fatality statistics ( r = .46). This indicates that as of the end of 2020, developing countries had reported fewer per capita infections and deaths compared to the wealthy countries such as those in the OECD.…”
Section: Public Health and The Covid‐19 Crisis: The Limits Of Individualism And Individual Explanations Of Behaviourmentioning
confidence: 99%
“…Based on the numbers of confirmed cases, deaths, and positive COVID‐19 tests (both aggregate and per capita), along with the number of tests per thousand people, the Asian‐Pacific region of the world has been considered most successful in pandemic mitigation, due in large part to successful public health systems, early border closing, and compliance in the general populous (Lowy Institute, 2021 ; Roser, Ritchie, Ortiz‐Ospina, & Hasell, 2020 ). Supporting this, research from Liu ( 2021 ) found a distinct positive correlation between collectivism and successful virus mitigation in terms of significantly lower COVID‐19 infection and fatality rates. On the other hand, Western nations with paradoxically higher human development indices and higher individualism exhibited general failures in handling COVID‐19.…”
Section: Introductionmentioning
confidence: 78%
“…Indeed, Study 2 shows that individualism had a negative impact on the extent to which participants indicated intentions to get vaccinated against COVID-19 when death was accessible, while collectivism and mortality salience were shown to have a positive impact on health intentions in both studies. This pattern of results may serve to explain differential pandemic-related outcomes in countries with varying levels of individualist or collectivist identity (e.g., Hofstede, 2011;Hofstede et al, 2010;Liu, 2021;Lowy Institute, 2021). Importantly, our studies indicate that using a well-validated means of priming the notions of individualism and collectivism (see Oyserman & Lee, 2008) successfully interacted with mortality awareness to bolster adaptive health behaviour intentions, supporting the efficacy of the TMHM for encouraging the behaviours necessary to reach the conclusion of this pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations